Short term results of philtrum reconstruction with an orbicularis oris muscle flap in cleft patients. Issue 6 (June 2020) - Wei, Jiao; Deng, Ning; Herrler, Tanja; Zhang, Yi; Li, Qingfeng; Hua, Chenqing; Dai, Chuanchang
Abstract: Purpose: In the treatment of philtral ridge deficiency in cleft lip patients, optimal results are difficult to obtain due to visible scarring following surgery. The purpose of this article is to introduce a novel strategy for philtrum reconstruction along with an evaluation of postoperative outcomes of this technique. Method: All patients with a deficiency of the philtrum underwent reconstruction of the philtral ridge and upper lip using an orbicularis oris muscle flap with a specific re-suturing technique in our study. The convexity of the philtral ridge was evaluated pre- and postoperatively at rest and while puckering using patient photography as well as three-dimensional simulation technology. Postoperative outcomes and complications were assessed during follow-up, including a patient satisfaction survey. Results: Thirty cleft lip patients underwent treatment in this study using a specific orbicularis oris muscle re-suturing technique. The average age of the 13 male and 17 female patients was 31.5 years. The follow-up period ranged from 6 months to 3.5 years with an average of 10.3 months. Postoperative results showed an aesthetic reconstructed philtral ridge with stable outcome. Complications included acute infection (1 case) and temporary stiffness of smile (3 cases). No systemic complications occurred. All patients were satisfied with their results, and none required further surgery. Conclusion: We propose a simple, effective, and reproducible technique involving an orbicularis oris muscle flap for the creation of the philtral column in secondary cleft lip deformity. Our approach allowed aesthetically pleasing and stable outcomes. Although the short-term results of the philtrum reconstruction seem to be adequate there is no information on the long-term situation, and therefore no general recommendation to adopt this method can be given.